Acceptance of COVID-19 vaccine booster dose among the people of Bangladesh: A cross-sectional study - Debendra Nath Roy; Shaheb Ali; Ashish Kumar Sarker; Ekramul Islam; Md. Shah Azam (Heliyon, 2023)
Vaccine booster dose (VBD) provides a potential therapeutic alliance in preventing breakthrough infection and new variant's arrival while preserving long-lasting host immunity. This study aimed to analyze COVID-19 VBD willingness and identified the key determinants of VBD acceptance among the general people of Bangladesh. This survey-based study applied a quantitative research paradigm. A validated, anonymous, and multi-item questionnaire was adopted through a theoretical review of pertinent literature on the topic. Data were collected between August 2022─October 2022, and sampling was done randomly. A total of 704 individuals were invited via face-to-face interview approach; however, 13.8 % of them declined to give consent, which resulted in the participation of 607 potential respondents. The main outcome measure was COVID-19 VBD acceptance willingness. Binary logistic regression analysis was conducted to rationalize the study's objectives. The pooled COVID-19 booster vaccine acceptance rate was 70.0 % (95 % confidence Interval [CI]: 67─73) among Bangladeshi people. An analysis of binary logistic regression revealed that, out of 14 potential factors, “efficacy”, “repeated immunity”, ”communication”, and “trust” showed highly significant positive association (adjusted odds ratio [aOR ] = 2.151 95 % CI: 1.391─ 3.508, aOR = 2.033 95 % CI: 1.299─ 3.181, and aOR = 2.552 95 % CI: 1.557─4.183 respectively, p<0.01), and “equal safety”, “risk-benefit ratio” and “community protection” had significant positive association (aOR = 1.739 95 % CI: 1.070─2.825, aOR = 1.712 95 % CI: 1.116─2.627, and aOR = 1.628 95 % CI: 1.395─0.998, p<0.05) with VBD acceptance. However, post-vaccination “side effects” showed significant negative (aOR = 0.393 95 % CI: 0.237─0.674, p<0.01) associations with VBD acceptance. The odds of accepting the COVID-19 vaccine booster was found 1.26, and it was found insignificant (p>0.05) in the Chi-squared test. Bangladeshi people expressed a moderately high level response to COVID-19 VBD acceptance. A positive attitude towards the COVID-19 VBD is an outcome of this study, regardless of the circumstances, as far as safety, efficacy, perceived health benefits, communication, trust, and community resistance are concerned. Post-vaccination side effects fear was the primary reason for booster dose skepticism as well as a barrier to administering booster shots. The confidence in COVID-19 VBD will be boosted when mass people are effectively communicated and vaccine's data become more available publicly.